Analisis Permasalahan Guru dan Siswa Terkait Pembelajaran Teams Games Tournament (TGT) dan Student Teams Achievement Division (STAD) Terhadap Motivasi Prestasi dan Prestasi Belajar Biologi - Siti Jamilah; Didimus Tanah Boleng; P M Labulan (Al-Hayat: Journal of Biology and Applied Biology, 2018)
This needs analysis aims to determine the problems that occur in Biology learning activities at SMAN1 Anggana. Application of learning models that suit students' needs. The research sample in this analysis is a class X student at SMAN 1 Anggana. The results of the observations showed that as many as 50.00% of the students' daily daily test results used the lecture method. This is because several things include students not paying attention to the teacher during the learning process, students playing with their peers, and monotonous learning. The teacher states that students tend not to ask questions in learning. In addition, the problem that is also faced is that there are still many teachers who apparently have not implemented learning models that can make students more active so students tend to be saturated. The way that can be taken to overcome this problem is by applying the team games tournament (TGT) learning model and the student teams achievement division (STAD). From the observations in the form of analysis of the problems of Biology teachers and students of SMAN 1 Anggana, it can be concluded that the ability of teachers to overcome problems in learning needs to be improved so that students are more active and happy to learn biology.